2015
DOI: 10.1039/c5cc01241d
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive room temperature NH3 sensor based on a graphene–polyaniline hybrid loaded on PET thin film

Abstract: This research was motivated by the need to develop a smart ammonia (NH3) sensor based on a flexible polyethylene terephthalate (PET) thin film loaded with a reduced graphene oxide-polyaniline (rGO-PANI hybrid) using in situ chemical oxidative polymerization. The sensor not only exhibited high sensitivity, good selectivity and a fast response at room temperature but was also flexible, cheap and had wearable characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(63 citation statements)
references
References 33 publications
2
61
0
Order By: Relevance
“…A large specific surface area (as shown in Figure 8) due to that the PANI nanoparticles and chains are anchored on the surface of GN, is benefit to the adsorption of NH 3 gas on the composite surface and the deprotonation at the interface of the composite. 29 Consequently, the response-recovery speed would be enhanced. In addition, the GN provides high conductivity and carriers mobility, and the electron transfer energy between PANI and GN is relatively lower (∼101 meV).…”
Section: Resultsmentioning
confidence: 99%
“…A large specific surface area (as shown in Figure 8) due to that the PANI nanoparticles and chains are anchored on the surface of GN, is benefit to the adsorption of NH 3 gas on the composite surface and the deprotonation at the interface of the composite. 29 Consequently, the response-recovery speed would be enhanced. In addition, the GN provides high conductivity and carriers mobility, and the electron transfer energy between PANI and GN is relatively lower (∼101 meV).…”
Section: Resultsmentioning
confidence: 99%
“…The sensor based on the nanostructured PANi has high specific surface area, which provides high sensitivity and fast response [7,12,13]. To improve the stability, sensitivity, and response time of the sensors, the PANi with different dopants were synthesized in the structure by coating its layers with different nanostructures such as nanoparticles [14,15], graphene, which comprise 2D arrays of carbon atoms [16], or nano-thin film on microstructure arrays [17]. The Pd possesses an electronic open-shell configuration 4d 9 5s 1 with 0.95 eV higher in energy compared with the closed-shell configuration 4d 10 5s 0 [18].…”
Section: Introductionmentioning
confidence: 99%
“…room (≤ 45˚C), not only avoids the heating 30 assembly but also makes the sensor setup simpler, portable, and cheaper. Khuspe et al reported that the incorporation of metal 95 oxides into polymer matrix greatly modify the microstructure and the mechanical properties of original polymer 26 and improves the sensing performance of sensor. polyaniline (PAni), polypyrrole, polythiophene etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The resulting mixture was kept at room temperature for 3 h followed by continuous stirring. The resulting film was washed in distilled water to eliminate the low molecular weight organic intermediates and dried at the ambient temperature and used for further studies.The synthesis process for the development 55 ofPAni/α-Fe 2 O 3 nanocomposite on PET substrate isillustrated thorough Scheme 1 26,29. To get emeraldine base form of PANi; de-doping of salt form takes place with 0.1 M NH 4 OH solution and at same time PET substrates were vertically dipped in the beaker.…”
mentioning
confidence: 99%